Agrobacterium-Mediated Transformation of the Recalcitrant Vanda Kasem’s Delight Orchid with Higher Efficiency - Gnasekaran, Pavallekoodi; Antony, Jessica Jeyanthi James; Mohammad, Jasim Uddain; Subramaniam, Sreeramanan (Hindawi Publishing Corporation, 2014)
The presented study established Agrobacterium-mediated genetic transformation using protocorm-like bodies (PLBs) for the production of transgenic Vanda Kasem’s Delight Tom Boykin (VKD) orchid. Several parameters such as PLB size, immersion period, level of wounding, Agrobacterium density, cocultivation period, and concentration of acetosyringone were tested and quantified using gusAgene expression to optimize the efficiency of Agrobacterium-mediated genetic transformation of VKD’s PLBs. Based on the results, 3-4mm PLBs wounded by scalpel and immersed for 30 minutes in Agrobacterium suspension of 0.8 unit at